Community-based baseline survey regarding prevalence of anemia among females of different age categories under Anemia Mukt Abhiyan in District Ambala, Haryana - Singhal, Joy; Kharab, Minakshi; Karol, Sunidhi; Abhishek; Hari, Sunil (International Journal Of Community Medicine And Public Health, 2023)
Background: Anemia is the most common micronutrient deficiency. Despite repeated efforts taken under the national program, high prevalence of anemia still observed across various life stages of females in India over the past two decades. Methods: This cross-sectional study aimed to discern the prevalence of anemia in the non-pregnant and non-lactating females of Ambala, Haryana, between the ages of 6 months to 49 years using the gold standard cyan-met-hemoglobin method. Results: A total of 1, 21, 202 study subjects, with a mean age of 28.9±19.3 years were tested for hemoglobin across 524 villages, out of which 97,305 (80.1%) females were found to be anemic with mean hemoglobin level of 10.8±1.4 gm% with 53.2% of all females being moderately anemic. Conclusions: This study reported that anemia is extremely prevalent in all walks of life of females. Multipronged strategy is to be followed to curb anemia from various age groups of females.